Travel behavior among Malaysian gays : A comparison between Malay, Indian and Chinese ethnicities / Sumithra Retnam - Retnam, Sumithra (2012)
To date, little research has been completed on the Malaysian gay market segment. Their preferences are almost unknown when it comes to travelling, such as their destination choice, motivation, and activities. As the gay market is known worldwide to be a lucrative market segment, an in-depth insight on their travel behavior is crucial. This study aims to provide marketers within the tourism industry with a comprehensive understanding on this rewarding market segment. As Malaysia is a multi-ethnicity nation, the preferences of each Malaysian cannot be generalized. As such, this study provides an overall view of the Malaysian Gay Travelers and further discusses the specific consumer behavior and preferences by individual ethnicities.